Diagnostic yield of medical thoracoscopy in diagnosis of exudative pleural effusion: One year prospective study - Sabah A. Mohamed; Marwa M. Shaban (Egyptian Journal of Chest Disease and Tuberculosis, 2014)
Background: Differential diagnosis of pleural disease is often a lengthy process fraught with pitfalls. Contrary to thoracocentesis and closed pleural biopsy, thoracoscopy permits biopsy with direct visualization. Medical thoracoscopy increases the diagnostic yield in patients with pleural disease when thoracocentesis and closed pleural biopsy are non diagnostic. Aim of the work: This study investigated diagnostic yield of medical thoracoscopy for undiagnosed exudative pleural effusions over one year period. Patient and Methods: This study included 117 patients with undiagnosed exudative pleural effusions. All patients were subjected to written informed consent, full history taking, clinical examination, plain chest X-ray, CT chest and tuberculin skin test. Diagnostic pleural aspiration was done with pleural fluid chemical and cytological analysis. Patients with unhelpful pleural fluid analysis underwent medical thoracoscopy. Results: Regarding thoracoscopic pleural biopsy histopathology, out of 117 patients, 55 were diagnosed as malignant pleural mesothelioma, 26 diagnosed as metastatic adenocarcinoma, 1 diagnosed as spindle cell carcinoma, 5 diagnosed as lymphoma, 5 diagnosed as tuberculosis, 1 diagnosed as SLE, 2 diagnosed as sarcoidosis, 6 diagnosed as empyema and 16 diagnosed as chronic non specific pleurisy. There was a statistically significant difference between the histopathological subgroups as regards mean value of age and smoking prevalence but there was no statistically significant difference as regards sex. Regarding pleural fluid cytological analysis, 5 cases were positive for malignant cells and 7 cases showed atypical mesothelial cells. Overall complication rate after medical thoracoscopy was low with no reported mortality or major complications. Conclusion: Medical Thoracoscopy is a valuable diagnostic tool for undiagnosed exudative pleural effusion. It is a simple and safe procedure with low complication rate.